BEREBUT “BERKAH” SENDANG SELIRANG DALAM PERSPEKTIF BEBERAPA KOMUNITAS MASYARAKAT MUSLIM KOTA GEDE, YOGYAKARTA: Sebuah Upaya Mempromosikan Dialog Agama dan Budaya - waryono, waryono (P2KK LIPI, 2017)
This article discusses about cultural phenomenon called by sendang selirang. Sendang Seliran is the name of one of the local culture typical in Kota Gede Yogyakarta, which are still preserved. Sendang Seliran is a tradition of cleaning the pool in the former kingdom of Mataram environment early in Kota Gede. The tradition interpreted differently by the three groups in Kota Gede: Abangan, muslim students, and intellectual. The problem is the background why and what are the differences? Although different, why citizens of Kota Gede, remain in harmony? This paper departs from the framework developed by Clifford Geertz interpretive ethnography to understand a cultural event that occurs in the community. The results show that for people Abangan, Sendang Selirang are rites and ceremonies performed with religious emotion and have sacred properties. Turned out to be different meanings for groups of students who are represented by Muhammadiyah. For some activists Muhammadiyah, tradition nawu Sendang (Sendang Selirang) is part of superstition, heresy, and kurafat, so it should be avoided. As for the